Evaluation of the effects of Streptococcus salivarius M18 and K12 probiotic bacteria on the Streptococcus mutans in saliva: A randomized clinical trial - Firoozeh Nilchian; Mohammadreza Esrafili; Nafiseh Hosseini (Wolters Kluwer Medknow Publications, 2024)
Background: Various methods, including the use of probiotics, have been suggested to prevent caries. Caries, which is mainly caused by Streptococcus mutans, is one of the bacterial diseases that imposes a heavy cost on society. The present study was conducted to investigate the probiotic products available in Iranian pharmacies that are used for caries prevention. Materials and Methods: In this double-blind randomized clinical trial, 40 students of medicine and pharmacy were randomly allocated to two equal groups of intervention and control using random allocation software. The intervention group used a probiotic pill containing Streptococcus salivarius M18 and K12 bacteria every night before going to bed. The control group used a mouth freshener tablet with the same flavor as the probiotic tablet every night before going to bed. The data were analyzed by SPSS (version 24) software using descriptive statistics (central tendency and dispersion) and inferential statistics (paired t-test and independent t-test). Data were collected using Excel software, and statistical analyses were performed by SPSS software (version 24). Results: The mean number of S. mutans in the intervention group was 754.5 cfu/mm before the intervention and 1701.5 cfu/mm after the intervention, which showed a statistically significant difference (P < 0.05). In the control group, the mean S. mutans was 683 cfu/mm at the beginning of the intervention and 659 cfu/mm at the end of the intervention, which did not indicate a statistically significant difference (P > 0.05). Moreover, the normality of data was checked by the Kolmogorov-Smirnov test. Conclusion: The mean number of S. mutans bacteria in the group using probiotic tablets was significantly increased compared to those of the control group. However, further studies are suggested to evaluate these products.